Polarized light microscopic evaluation of remineralization by casein phosphopeptide-amorphous calcium phosphate paste of artificial caries-like lesion: An in vitro study - Shreyas Pradeepkumar Shah; Praveen N Birur (Wolters Kluwer Medknow Publications, 2015)
Introduction: Dental caries was considered to be an irreversible disease, but this concept of caries is changing because of the availability of many newer products for its treatment. One of such product is casein phosphopeptide-amorphous calcium phosphate (CPP-ACP). Aim: The present in vitro study was aimed to evaluate remineralization of artificial caries-like lesion by topical application of CPP-ACP paste. Materials and Methods: In this study, 40 caries-free premolar and molar teeth requiring extraction for orthodontic reasons and impactions were used. Artificial caries-like lesion was produced on sound enamel surface by immersing the samples in demineralizing solution for 96 h. Longitudinal sections were made through the white spot lesion with hard tissue microtome and were subjected to polarized light microscopic evaluation. The sections were divided into CPP-ACP group (Group I), positive control (Group II), and negative control (Group II). The Group I and Group II samples were subjected to 10 days of pH cycling, and all the samples were evaluated by polarized light microscopy. The lesion depth was calculated, and all the data was subjected to statistical analysis. Results: CPP-ACP group showed 27.306% decrease in lesion depth after 10 days of pH cycling. Conclusion: Based on the findings of this study, it can be concluded that the CPP-ACP paste can cause remineralization of white spot lesion and can be prescribed as topical application paste for the treatment of initial caries lesions.